The Study of the Main Factors that Affect the Job Satisfaction of Chinese Post-90s Employees of Returnees - LI, KUNJING (2017)
The aim of the dissertation is to study the affecting factor of the job satisfaction of Chinese post-90s employees of returnees. The high turnover rate of post-90s returnees in china, making many organizations to focus on the job satisfaction of this group. The post-90s generation have the distinctive character and work status, and they will be more special when they experience the education abroad. The post-90s returnees might be influenced by cross-national culture so that forming their own values compared with the old generation. Meanwhile, many organization plans some policies for the post-90s employees of returnees. These factors might have an influence in the job satisfaction of Chinese post-90s returnees. the study is going to research whether work reward, work itself, organization culture, organizational policy and work- related value mainly effect on the job satisfaction of Chinese post-90s returnees through questionnaire survey with 200 participants who are post- 90s employees of returnees. Overall, the work reward, work itself, organization culture and work-related value have a positive effect on the job satisfaction of Chinese post-90s returnees; the organizational policy for returnees cannot affect the job satisfaction.